Problem of Human Rights in World Politics: Three Indonesian Case Studies - Jemadu, Aleksis (Indonesian Journal of International Law, 2021)
The problems of human rights in the global political arena makes the interaction between the actors, even it is a state or non-state after the end of the cold war. In this article, the perspective of international and domestic is used to discuss the extent of the human rights affect those actors. In an international perspective, the emerging of global terrorism threat is start by the September 11th 2001 accident whose be the new challenge for the promotion of human rights because the dominant states will feature the domestic security and international instead of the honor of the human rights. In that point, United States of America’s role and its allies is getting much intention in this article. In domestic perspective, the authors take three cases experience of Indonesia in the consolidation of democracy in the promotion of human rights whose still questionable. Concluded that the promotion of human rights is must be the part of the integral from the democracy consolidation process.